2007
DOI: 10.1001/archpsyc.64.11.1270
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of White Matter Integrity in the Inferior Longitudinal Fasciculus in Adolescents With Schizophrenia as Revealed by Fiber Tractography

Abstract: Our findings, which benefited from greater image resolution and methodological control than previous studies conducted in adolescents with schizophrenia, provide strong evidence for lower white matter integrity in the left ILF, particularly for patients with a history of visual hallucinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
113
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(130 citation statements)
references
References 73 publications
16
113
0
1
Order By: Relevance
“…Differences in RD are less examined, yet to date increases have been detected in the external capsule (Seal et al, 2008), in the left inferior temporal and left occipital lobe (Ashtari et al, 2007), in temporal WM (Koch et al, 2011), and in the middle cerebellar peduncle (Okugawa et al, 2006), and increased mean diffusivity has been detected in the splenium of the corpus callosum (Foong et al, 2000). The regions reported in these studies were also found in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in RD are less examined, yet to date increases have been detected in the external capsule (Seal et al, 2008), in the left inferior temporal and left occipital lobe (Ashtari et al, 2007), in temporal WM (Koch et al, 2011), and in the middle cerebellar peduncle (Okugawa et al, 2006), and increased mean diffusivity has been detected in the splenium of the corpus callosum (Foong et al, 2000). The regions reported in these studies were also found in this work.…”
Section: Discussionmentioning
confidence: 99%
“…This is not the first study pointing to altered diffusion parameters in the thalamus or thalamocortical pathways. DTI findings supporting altered integrity of thalamocortical connectivity in schizophrenia include controversial alterations of fractional anisotropy in the anterior limb of the internal capsule (ALIC) Kubicki et al, 2005;Mamah et al, 2010;Sprooten et al, 2009;Sussmann et al, 2009;Zhang et al, 2010;Zhou et al, 2008, but see Ashtari et al, 2007;Kito et al, 2009;Kyriakopoulos et al, 2008;Szeszko et al, 2005;White et al, 2007 for negative findings in younger individuals and Beasley et al, 2009 for lack of evidence of myelin abnormalities post-mortem), of the tracts connecting to the LPFC (Kim et al, 2008;Oh et al, 2009) and altered FA (Hashimoto et al, 2009) or mean diffusivity in the thalamus itself (Agarwal et al, 2008;Rose et al, 2006;Spoletini et al, 2011). Kim et al (2007) have performed a similar DTI study, with an identical a-priori hypothesis, but found only differences in the thalamic CDR defined by connectivity to the orbitofrontal, parietal, and medial prefrontal cortices.…”
Section: Discussionmentioning
confidence: 99%
“…Philips Medical Systems (Best, Netherlands) offers a similar software package called PRIDE (Philips Research Integrated Development Environment). Others (e.g., (Ashtari et al, 2007) have used elaborate registration algorithms that permit overlaying of tracts-ofinterest derived from tractography models produced by programs such as DTIStudio, MedINRIA, or PRIDE onto scalar FA maps to determine the structural integrity of the selected tracts. Each of these methods demonstrated the potential utility of using quantitative tractography.…”
Section: Introductionmentioning
confidence: 99%